The Problems of Implementation of Electronic GMS on the Making of Relaas Notary Deed - Syifa Rana Tsary; Silaas Oghenemaro Emovwodo (JURNAL AKTA, 2023)
This study examines the development of the digitalization era in the legal field, especially the electronic General Meeting of Shareholders (GMS) regulated by law. The formulation of the research problem is how the electronic GMS according to positive law in Indonesia and how the impact on the notarial deed related to the implementation of the electronic GMS. The research method used is normative and literature study, based on primary legal materials (statutory regulations), secondary legal materials (scientific works, journals, books, documents and other literature), and tertiary legal materials (legal dictionaries). The results of this study are that the E-GMS has been legally enforced, because it is regulated in Article 77 of the Company Law and POJK Number 16/Pojk.04/2020, so that the organs of the Limited Liability Company can carry out the GMS as usual without being physically present in order to break the chain of the Covid-19 pandemic. Although the e-GMS arrangements have been clearly regulated in the legislation, the lex specialist derogat lex generalist principle cannot be ignored, Article 16 paragraph (1) letter (m) and Article 18 UUJN are still prioritized, so that the electronic deed of the GMS cannot be carried out or will resulting in the legal force of the proof being a private deed.